PENGARUH PROFITABILITAS DAN FREE CASH FLOW PADA KEBIJAKAN DIVIDEN DENGAN INVESTMENT OPPORTUNITY SET SEBAGAI MEDIASI - Raditya, Ida Bagus Putera; Sisdyani, Eka Ardhani (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
Research investigates the influence of profitability and free cash flow on dividend policy, with investment opportunity set as the mediating variable. The study involves companies listed in the SRI-KEHATI index as the research subjects. Purposive sampling using path analysis was employed, with 86 observations. The findings indicate that profitability does not have a significant effect on investment opportunity set. Conversely, free cash flow has a significant negative impact on investment opportunity set. Profitability also does not have a significant influence on dividend policy, while free cash flow has a significant positive effect on dividend policy. Investment opportunity set does not have a significant influence on dividend policy. However, the research results suggest that investment opportunity set acts as a mediating variable in the relationship between profitability, free cash flow, and dividend policy.